Peran Orang Tua dalam Mendampingi Proses Belajar yang Efektif terhadap Anak di Dusun Sumberejo, Waru - Rohima, Siti; Setyariza, Nur Ayu; Kusumawardani, Intan; Widayati, Sri Erna; Handayani, Yekti (TSAQOFAH, 2024)
In the learning process parents have a very important role in the learning process. Parents are the first and main educators of their children. Therefore, the first education that children receive is education from parents. Education for their children is education that is based on love for children. The task of educating children is a shared responsibility between father and mother who have the responsibility to act as educators for their children. The good and bad of a child can be seen from the parenting style provided by his parents. With this, fathers and mothers have responsibility for their children's education and all aspects of their lives from the time the children are small until they are adults. So parents have an obligation to accompany their children's learning process.